Dos direitos das comunidades tradicionais na perspectiva da Propriedade Intelectual - Borges, Ludymila Johann (2017)
This paper gives a brief examination on the collective rights in the perspective of intellectual property, and it aims to observe the concepts that involves the legal protection which traditional communities receive by verifying the comprehensiveness of their collective rights applied. Analyzing international conventions that regulate the economic life and the preservation of the collective goods of these communities. It also aims to investigate the cultural and economic development of traditional communities and how the sum resulting of intangible and cultural goods influences the knowledge of these people.